Sultan Muhammed, Sultan Süleymanşah, Sultan Arslanşah devrinde Irak Selçukluları tarihi ( 548- 572 / 1153-1176) - Çevik, Adnan (My University, 1995)
unknown
Keywords: Irak; Ortaçağ; Ortadoğu; Tarih; Tarih_Selçuklu Devleti